Therapeutic Effects of Tangshen Formula on Diabetic Nephropathy in db/db Mice Using Cytokine Antibody Array - Xue Mei Fan; Chun Lian Huang; Yi Ming Wang; Ning Li; Qiong Lin Liang; Guo An Luo (Journal of Diabetes Research)
Objective. Cytokines are essential promoters in the pathogenesis of diabetic nephropathy (DN) in type 2 diabetes. The following study investigates the adjustment mechanism of Tangshen formula (TSF) on cytokine expressions in db/db mice (DN animal model). Materials and Methods. Db/db mice were randomly divided into three groups. The treated groups were orally administered with TSF and losartan for 12 weeks. Biochemical and histological examinations were determined at 8 and 12 weeks posttreatment, while the cytokine antibody array analysis was applied to analyze the expression of 144 cytokines in kidney tissues at the end of the 12th week posttreatment. Results. TSF significantly reduced urinary albumin excretion and the levels of blood glucose, cholesterol, triglyceride, creatinine, and urea nitrogen. Furthermore, a significant decrease in glomerulus and mesangial area, as well as the downregulation of 24 cytokines and upregulated expressions of 5 cytokines, was found in the TSF-treated mice. Conclusions. The present study reveals that TSF could ameliorate the metabolic anomalies and renal injury in db/db mice. One of the important mechanisms for treatment of DN using the treatment of TSF is the control of the JAK/STAT signaling pathway via regulation of IL-2, IL-6, IL-13, Il-15, and IFN-γ expression.